2007
DOI: 10.1021/ma0615046
|View full text |Cite
|
Sign up to set email alerts
|

Single Wall Carbon Nanotube/Polyethylene Nanocomposites: Thermal and Electrical Conductivity

Abstract: The thermal and electrical conductivities in nanocomposites of single walled carbon nanotubes (SWNT) and polyethylene (PE) are investigated in terms of SWNT loading, the degree of PE crystallinity, and the PE alignment. Isotropic SWNT/PE nanocomposites show a significant increase in thermal conductivity with increasing SWNT loading, having 1.8 and 3.5 W/mK at a SWNT volume fraction of φ ∼ 0.2 in low-density PE (LDPE) and high-density PE (HDPE), respectively. This increase in SWNT/HDPE is more than additive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
229
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(241 citation statements)
references
References 28 publications
(52 reference statements)
10
229
1
1
Order By: Relevance
“…In a separate study we prepared SWNT/polyethylene composites using an adaptation of the coagulation method with up to 30wt% SWNT. 25 The improvement in thermal conductivity in the nanotube-rich pathway with 20wt% SWNT prepared by nitrogen gasification is greater than in the 30wt% SWNT/PE composite containing discrete SWNT. This illustrates the importance of reducing nanotube/polymer/nanotube contacts to increase the thermal conductivity in composites even at high SWNT loadings.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In a separate study we prepared SWNT/polyethylene composites using an adaptation of the coagulation method with up to 30wt% SWNT. 25 The improvement in thermal conductivity in the nanotube-rich pathway with 20wt% SWNT prepared by nitrogen gasification is greater than in the 30wt% SWNT/PE composite containing discrete SWNT. This illustrates the importance of reducing nanotube/polymer/nanotube contacts to increase the thermal conductivity in composites even at high SWNT loadings.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, while this paper demonstrates the concept with epoxy, this infiltration method is broadly applicable to various thermoplastics and thermosets, as long as the volume change upon polymerization or curing is small. SWNT/PE composite using discrete SWNT bundles (data from R. Haggenmueller et al 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although results for CNT polymer composites show strong improvement of κ at low CNT content, it is still significantly less than predicted by simple mixture rules and the reason is probably due to interfacial thermal resistance between the CNTs and the polymer matrix [12]. In this context, it is interesting to note that Haggenmueller et al [13] found 600% increase of κ by adding 20 vol % SWCNTs in high density polyethylene and that the increase was stronger than that predicted by a linear dependence on the SWCNT content. The latter suggests a percolation effect and…”
Section: Introductionmentioning
confidence: 90%
“…In addition, dispersion methods can vary greatly depending on the characteristics of matrix material. [16][17][18][19][20][21][22][23][24][25] While measurable increases in electrical conductivity can be achieved through addition of as little as 0.007 wt% CNTs to polymer matrices, 5 preparation of composites with conductivities >1 S cm -1 requires either higher loadings of CNTs (>10 wt%) [7][8][9][10][11][12][13] or specially-designed CNTs that facilitate dispersion in the matrix. 25 Thus, the fabrication of CNTpolymer composites with conductivities on par with highly conductive semiconductors and metals for applications such as electromagnetic interference shielding can be an expensive endeavor.…”
Section: Introductionmentioning
confidence: 99%